A study on load position control and vibration attenuation in crane operation using sub-actuator. (September 2019) - Lee, Dong-Hoon; Kim, Tae-Wan; Ji, Sang-Won; Kim, Young-Bok
The main purpose of any crane system is to move a load to a specified place. Accurate load positioning in the presence of unpredictable external factors is an important issue when operating a crane. Attenuation of load vibration during crane operation is immensely critical in order to satisfy rigorous requirements for safety and efficiency. When a crane is installed and operated on a vessel at sea, work conditions become even more difficult and thus require more stringent attention to load positioning and attenuation of load vibration. At sea, this process is complicated due to factors such as waves and wind, making accurate crane operation nearly impossible. For these reasons, active heave compensation systems have been developed to suppress the effects of disturbances raised from the harsh sea environment including vessel motions. This paper explores the suppression method of unexpected vertical vibration of load. Unlike past research on the topic, this research includes rope dynamics in the control system design for suppressing load vibration. In addition, this research considers uncertain disturbances—vessel motions not controlled by any active force that result in undesirable heave motion of a crane. Load motion is indirectly estimated using a load cell because we do not yet have any useful tool to measure it directly. In the considered crane system, two winches were used, one for moving the load and the other for suppressing residual vibration. To evaluate the proposed control strategy and system performance, several control techniques were applied: proportional–integral–derivative control, sliding mode control, and feedback linearization control methods.